Plasma pharmacokinetics, milk residue depletion profile, and milk withdrawal interval estimation following multiple-dose oral administration of meloxicam to lactating dairy goats - Mercer, Melissa A.; Zhang, Zhicheng; Clapham, Maaike O.; Wetzlich, Scott E.; Smith, Fauna L.; Rupchis, Benjamin A.; Lin, Zhoumeng; Tell, Lisa A. (Frontiers in Veterinary Science, 2025)
IntroductionMeloxicam is frequently administered orally to lactating dairy goats in an extra-label manner. However, since Food and Drug Administration (FDA)-approved withdrawal times have not been established, this raises concerns for potential drug residues in milk. This study aimed to estimate plasma pharmacokinetics, determine meloxicam residues in milk based on concentration versus time depletion profiles, and calculate estimated withdrawal interval (WDI) recommendations for meloxicam following multiple oral doses administered to lactating dairy goats.MethodsMeloxicam was administered to healthy mid-lactation dairy goats (n = 10) at 1 mg/kg orally every 24 h for a total of 6 doses. Meloxicam was quantified in plasma and milk samples using high-performance liquid chromatography (HPLC) with an ultraviolet detector. Plasma pharmacokinetic parameters were estimated using a non-compartmental approach, and theoretical milk elimination half-life was also estimated. Milk WDIs were calculated using the FDA tolerance limit method under various data simulation scenarios and compared to the standard FDA regulatory approach, which involves 10 animals with triplicate samples. Additional assessment included the European Medicines Agency (EMA) maximum residue limit (MRL) method and the theoretical terminal elimination half-life method.ResultsFollowing the final administered dose, the geometric mean plasma estimated T1/2 was 7.64 h (range 5.61–9.47 h), while the geometric mean milk theoretical estimated T1/2 was 6.96 h (range 5.47–9.56 h). WDI estimations using the FDA tolerance limit method targeting the analytical limit of detection (4 ng/mL) ranged from 70.1 to 82.8 h. The WDI estimated using the EMA MRL method targeting the EMA MRL (15 ng/mL) was 64.97 h. Monte Carlo simulation of single replicate data closely approximated WDI estimates from full triplicate datasets, whereas simulating additional virtual animals introduced relatively greater variability in the estimated WDI.ConclusionThis study estimated the plasma pharmacokinetic parameters and theoretical milk residue depletion profiles for meloxicam following multiple oral doses administered to healthy lactating dairy goats. The theoretical elimination half-life of meloxicam for milk is shorter for goats than cattle, resulting in shorter estimated WDIs for the same dosing regimen. From a food safety perspective, meloxicam cattle withdrawal times (WDTs) or estimated WDIs may be appropriately conservative for application to goats when properly adjusted for dose, route, and regulatory tolerances/MRLs.